2019
DOI: 10.3201/eid2501.180534
|View full text |Cite
|
Sign up to set email alerts
|

Meat and Fish as Sources of Extended-Spectrum β-Lactamase–Producing Escherichia coli, Cambodia

Abstract: We compared extended-spectrum β-lactamase–producing Escherichia coli isolates from meat and fish, gut-colonized women, and infected patients in Cambodia. Nearly half of isolates from women were phylogenetically related to food-origin isolates; a subset had identical multilocus sequence types, extended-spectrum β-lactamase types, and antimicrobial resistance patterns. Eating sun-dried poultry may be an exposure route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…It enables phylogenetic trees to be quickly reconstructed from a large number of genomes without the burden of multiple sequence alignments (see e.g. 2,29, [44][45][46][47][48][49][50][51][52]. This report confirms this view by showing that proper evolutionary distances can be easily derived from MH p-distance estimates, therefore enabling accurate phylogenetic inferences.…”
Section: Discussionsupporting
confidence: 63%
“…It enables phylogenetic trees to be quickly reconstructed from a large number of genomes without the burden of multiple sequence alignments (see e.g. 2,29, [44][45][46][47][48][49][50][51][52]. This report confirms this view by showing that proper evolutionary distances can be easily derived from MH p-distance estimates, therefore enabling accurate phylogenetic inferences.…”
Section: Discussionsupporting
confidence: 63%
“…Sellera and colleagues [ 40 ] reported isolation of ESBL (CTX-M)-producing E. coli from wild fishes of a polluted area in the South Atlantic coast of Brazil. ESBL-producing E. coli of identical genotypes have been reported from fish, chicken and infected patients in Cambodia [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Phnom Penh, among fish, pork, and chicken samples, bacterial plasmids carrying CTX-M type ESBL genes also carry resistance genes for multiple other classes of antibiotic, including aminoglycosides, fluoroquinolones, and co-trimoxazole (Nadimpalli et al, 2019a). Furthermore, a link has been made between CTX-M type ESBL producing E. coli isolated from fish, pork, and chicken in markets from Phnom Penh, and isolates colonising humans (Nadimpalli et al, 2019b). A subsequent concern is that injudicious use of any of these classes of antibiotic will co-select for resistance genotypes against the others.…”
Section: Discussionmentioning
confidence: 99%
“…The mcr-1 gene has been reported in human isolates collected in Cambodia in as early as 2012 (Stoesser et al, 2016) and has also been identified in Salmonella spp. and E. coli isolated from market food in Phnom Penh (Nadimpalli et al, 2019a;Nadimpalli et al, 2019b). The transmission pathways have not yet been clarified, but the role of food and food animals in the human acquisition of mcr-1 carrying Enterobacteriaceae is believed to be significant, and raises fears for the future of one of our "last-resort" antibiotics (Nhung et al, 2016).…”
Section: Discussionmentioning
confidence: 99%